Regulation of Fibrinolysis in the Development of Atherothrombosis: Role of Adipose Tissue - Juhan-Vague, I.; Alessi, M.C. (Thrombosis and Haemostasis, 1999)
Among the list of coronary risk factors, it has recently been proposed that fibrinolytic system impairment, due to increased plasminogen activator inhibitor-1 (PAI-1) levels in plasma, could predict complications of atherosclerosis. The fibrinolytic system1 is regulated by a balance between activators and inhibitors. PAI-1, which inhibits t-PA and u-PA, is the main inhibitor of plasminogen activation. An increased PAI-1 concentration induces a reduction in plasmin formation and leads to fibrin accumulation.2-5 PAI-1 also induces changes in vessel wall remodeling through the activation of metalloproteinases and growth factors and the degradation of the extracellular matrix.4 In addition to its antiprotease activity, PAI-1 also participates in the cellular adhesion and migration processes. Because it binds to vitronectin in the same part of the molecule as vitronectin receptor or u-PA receptor, it mediates the release of cells from their substrate.6,7 All of these properties indicate that PAI-1 can be involved in tissue remodeling and thrombotic processes and, therefore, participates in the development of atherothrombosis.In plasma, an elevated PAI-1 concentration is presently considered a risk factor for coronary vascular events. It appears that PAI-1 is an inducible target controlled for in insulin resistance and obesity, which are situations that favor the development of atherothrombosis. It has been postulated that PAI-1 could contribute to an increased susceptibility to atherothrombosis in insulin-resistant patients. The production of PAI-1 by adipose tissue has recently been demonstrated. The elucidation of the regulation of PAI-1 synthesis and the identification of factors responsible for increased plasma PAI-1 concentration in the insulin-resistant state might lead to therapeutic concepts for the prevention of atherothrombosis.